Analysis of Factors Influencing the Performance of Accounting Information Systems at Village Credit Institutions in Abiansemal District - Ni Putu Linda Novita Dewi; I Ketut Suryanawa (International Journal of Economics, Management and Accounting, 2025)
The rapid development of information technology has encouraged Village Credit Institutions (LPDs) to adopt Accounting Information Systems (AIS) as an effort to enhance operational efficiency and effectiveness. However, the implementation of AIS in several LPDs in Abiansemal District still faces various challenges, such as data input errors and lack of system integration. This study aims to analyze the influence of system development formalization, organizational size, user involvement, training and education, as well as personal technical skills on the performance of accounting information systems. The research method used is quantitative with a survey approach. The sample consists of 96 respondents, comprising leaders and managers of 32 active LPDs in Abiansemal District, Badung Regency. The data analysis techniques include validity and reliability tests, classical assumption tests, multiple linear regression analysis, coefficient of determination test, F-test, and t-test using SPSS software. The results show that all five independent variables—system development formalization, organizational size, user involvement, training and education, and personal technical skills—have a simultaneous and partial positive and significant influence on the performance of accounting information systems. The coefficient of determination indicates that 55.8% of the variation in AIS performance can be explained by these five variables.